Establishment and Application of Loop-Mediated Isothermal Amplification Assays for Pathogens of Rice Bakanae Disease - Xinchun Liu; Yan Wang; Yating Zhang; Jingzhao Xia; Chenxi Liu; Yu Song; Tao Han; Songhong Wei; Wenjing Zheng (Agriculture)
Rice bakanae disease (RBD), a major threat in rice-cropping nations, can reduce rice yield and quality. As it is a seed-borne disease, effective seed detection is crucial. Loop-mediated isothermal amplification (LAMP) can rapidly and specifically amplify DNA at a constant temperature with high sensitivity. This research uses LAMP to develop rapid RBD pathogen detection systems. Primers were designed targeting the NRPS31 gene of Fusarium fujikuroi and conserved TEF1α sequences of Fusarium asiaticum, Fusarium proliferatum, and Fusarium andiyazi. These reactions at 60 °C for 60 min had a detection limit of 100 pg·μL−1, and LAMP proved applicable in field trials.